A Comprehensive Review of Mucormycosis: A Black Fungus Disease Causing Mayhem in COVID-19 Patients - Nema, Mr. Prakhar (International Journal of Pharmaceutical & Biological Archive, 2023)
Mucormycosis is an in frequent devious fungal infection characterized by infarction and necrosis of host tissues that result from invasion of the vasculature by hyphae. The mortality rate of this infection is so high compared to COVID-19, because the maximum death cases were observed due to this infection occurred after post-recovery of COVID-19 or simultaneously. The urge of death cases Mucormycosis is acknowledged as an epidemic in various states of India.